Culturas urbanas y prácticas pastorales: evangelización, complejidad urbana y conversión pastoral - Mancera Casas, Pbro. Jaime Alberto (2023)
The city and its cultures, its dynamics, its subjects, its structures and networks, and the whole network of relationships that this involves, are the “complexity” that the Church community must continually learn to accept, respect, share and support in the exercising of evangelical praxis and theological exercise.